A new species of Crossodonthina Yosii (Collembola, Neanuridae) from Central-South China, with the redescription of C. hainana Xiong, Chen & Yin, 2005 - Jiang, Jigang; Wang, Qingyun (Zootaxa, 2025)
A new species of Crossodonthina Yosii is described from Mountain Jiuyi National Nature Reserve, Hunan Province, Central-south China. Crossodonthina jiuyishanensis sp. nov. is characterized by body tubercles well differentiated; all body chaetae smooth and pointed; cephalic chaeta O present and included in tubercle Fr; tubercle Oc with 3 chaetae; cephalic tubercles Dl, L and So separated from each other; cephalic chaeta Di2 included in tubercle Di; mandible complex, with two basal teeth and six main branches; maxilla with three lamellae; tubercles Di, De and Dl on Th. I with 1, 2, 2 chaetae respectively; tubercle Di on Abd. I–III each with 3 chaetae, tubercle L on Abd. I–III each with 7–9 chaetae (6–8+s). We also record and redescribe Crossodonthina hainana Xiong, Chen & Yin, 2005 from Hunan Province, China. Finally, a key to all Crossodonthina species is provided.